Author Correction: Acylated-acyl carrier protein stabilizes the Pseudomonas aeruginosa WaaP lipopolysaccharide heptose kinase. Issue 1 (December 2018) - Kreamer, Naomi; Chopra, Rajiv; Caughlan, Ruth; Fabbro, Doriano; Fang, Eric; Gee, Patricia; Hunt, Ian; Li, Min; Leon, Barbara; Muller, Lionel; Vash, Brian; Woods, Angela; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.